Enhancing the metabolic benefits of exercise: Is timing the key? - Bennett, Samuel; Sato, Shogo (Frontiers in Endocrinology, 2023)
Physical activity represents a potent, non-pharmacological intervention delaying the onset of over 40 chronic metabolic and cardiovascular diseases, including type 2 diabetes, coronary heart disease, and reducing all-cause mortality. Acute exercise improves glucose homeostasis, with regular participation in physical activity promoting long-term improvements in insulin sensitivity spanning healthy and disease population groups. At the skeletal muscle level, exercise promotes significant cellular reprogramming of metabolic pathways through the activation of mechano- and metabolic sensors, which coordinate downstream activation of transcription factors, augmenting target gene transcription associated with substrate metabolism and mitochondrial biogenesis. It is well established that frequency, intensity, duration, and modality of exercise play a critical role in the type and magnitude of adaptation; albeit, exercise is increasingly considered a vital lifestyle factor with a critical role in the entrainment of the biological clock. Recent research efforts revealed the time-of-day-dependent impact of exercise on metabolism, adaptation, performance, and subsequent health outcomes. The synchrony between external environmental and behavioural cues with internal molecular circadian clock activity is a crucial regulator of circadian homeostasis in physiology and metabolism, defining distinct metabolic and physiological responses to exercise unique to the time of day. Optimising exercise outcomes following when to exercise would be essential to establishing personalised exercise medicine depending on exercise objectives linked to disease states. We aim to provide an overview of the bimodal impact of exercise timing, i.e. the role of exercise as a time-giver (zeitgeber) to improve circadian clock alignment and the underpinning clock control of metabolism and the temporal impact of exercise timing on the metabolic and functional outcomes associated with exercise. We will propose research opportunities that may further our understanding of the metabolic rewiring induced by specific exercise timing.